TIR domain of bovine TLR4 gene in Frieswal crossbred cattle: An early marker for mastitis resistance - DEB, RAJIB; SINGH, UMESH; KUMAR, SUSHIL; KUMAR, ARUN; SHARMA, ARJAVA; MANN, SANDEEP; SINGH, RANI (The Indian Journal of Animal Sciences, 2013)
Toll like receptor 4 (TLR4) is implicated as a receptor mediating cellular activation in response to bacterial lipopolysaccharides (LPS) of gram negative organisms which is the principal pathogen associated molecular patterns (PAMPs) of TLR 4. Thirty-one single nucleotide polymorphisms (SNP) were detected in bovine TLR4 gene. The SNP (g.9788C>T) found in the Toll IL-1 receptor (TIR) domain of the bovine TLR4 is reported to be associated with mastitis in earlier studies. In the present study we have amplified the TIR domain containing the above SNP site from Frieswal (Holstein Friesian Ã— Sahiwal) crossbreed cattle blood genomic DNA. The amplified products of 126 unrelated Frieswal TIR domain of TLR4 gene were digested with Hinf I restriction enzyme and genotyping was analyzed. Our studies revealed that CC alleles (0.97) are more prevalent than TT alleles (0.03) in Frieswal genome.